Technological approaches to providing safe drinking water for rural and remote areas. (10th September 2008) - Prabhakar, S.
Provision of safe drinking water is one of the key drivers in our technological pursuits. A number of habitations are suffering from a variety of water quality problems such as excess salinity, iron, arsenic, fluoride, nitrate and microbial contamination. Simplicity of operation, less dependence on external sources of power supply, minimisation of wastewater, etc., are some of the ground rules to ensure reliability and sustainability of water purification technologies/devices. The experience over the last two decades has indicated that the objective of providing safe drinking water in totality can be achieved only with the technologies in tune with the village environment and the total participation of the user group. Domestic water purifier based on ultrafiltration can be used as a point-of-use device in almost all households to provide microbiologically safe drinking water. With suitable modifications, these devices can be used for removal of contaminants such as iron, and marginal contamination of fluorides and arsenic. The use of reverse osmosis can tackle salinity and other contaminants. Safe quality water is costlier due to the use of the device and hence its use should be only to the extent required. It is necessary therefore to promote quality linked usage of water to ensure sustainability and reliability.